The Case of the Black-Gloved Rapist: Defining the Public Defender's Role in the California Courts, 1913-1948 - Mayeux, Sara (2010)
This essay traces [these] two competing visions of the public defender in California from 1913 to 1948, and examines how and why the second view ultimately prevailed, at least doctrinally. On the ground, some public defenders may have continued to see themselves primarily as public servants, and some trial judges may have endorsed this view. But in the 1940s, California appellate judges rejected the Progressive ideal of the public defender. They constructed the public defender as an opponent of the state, leaving intact (at least in theory) the American adversary system of criminal justice. In so doing, they followed the direction of the United States Supreme Court, which had recently issued a robust defense of adversary process in the landmark right-to-counsel case of Powell v. Alabama